2019
DOI: 10.1037/bar0000118
|View full text |Cite
|
Sign up to set email alerts
|

Representation of women in behavior analysis: An empirical analysis.

Abstract: As in other disciplines, women were underrepresented in behavior analysis in its early decades. Over the years, multiple articles have documented increasing trends in women's representation in behavior analysis in areas such as contributions to the scholarly literature and participation in professional associations. The purpose of the present article was to extend this line of investigation by more comprehensively evaluating the participation of women in behavior analysis in a variety of areas and by analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…It is difficult to identify with certainty the cause(s) of increased representation of women and junior authors. Perhaps women academics in “younger cohorts” (i.e., ages 25–34 and 35–44; see Nosik et al, 2019) are successfully publishing more frequently and are beginning to represent a greater proportion of behavior‐analytic faculty and researchers. If this is the case, it would be surprising, and indeed concerning, if there was not a strong presence of women in article authorship.…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to identify with certainty the cause(s) of increased representation of women and junior authors. Perhaps women academics in “younger cohorts” (i.e., ages 25–34 and 35–44; see Nosik et al, 2019) are successfully publishing more frequently and are beginning to represent a greater proportion of behavior‐analytic faculty and researchers. If this is the case, it would be surprising, and indeed concerning, if there was not a strong presence of women in article authorship.…”
Section: Resultsmentioning
confidence: 99%
“…Although the body of literature regarding women's issues in behavior analysis is relatively meager (i.e., approximately 40 publications in academic journals over the past 40 years), two recent contributions are worthy of note. First, at the inaugural WIBA conference, Melissa Nosik presented her recent analysis of data on women's representation in various career milestones-including professional recognition (e.g., awards, appointments), professional organization leadership, invited presentations, editorial board appointments, publication trends, faculty hires, and certification-and shared an overall career milestone analysis (Nosik, Luke, & Carr, 2018). Nosik et al (2018) found women were underrepresented in the categories of professional recognition, invited presentations, and editorial board appointments.…”
Section: Existing Issues On Gender Equalitymentioning
confidence: 99%
“…Despite being underrepresented, women's participation showed dramatic growth in editorial board appointments and publication trends. From 1978 to 2016, the percentage of women authors increased in the Journal of Applied Behavior Analysis (JABA) from 17.7% to 61.5% and in the Journal of the Experimental Analysis of Behavior (JEAB) from 7.0% to 35.2%; however, a decrease was noted in The Behavior Analyst (TBA) from 27.0% to 24.2% (Nosik et al, 2018). From 1979 to 2016, JABA increased women editorial board members from 25% to 41%, and JEAB increased representation from 7.7% to 29.4%.…”
Section: Existing Issues On Gender Equalitymentioning
confidence: 99%
See 2 more Smart Citations